Bipolaris sorokiniana-Induced Black Point, Common Root Rot, and Spot Blotch Diseases of Wheat: A Review - Al-Sadi, Abdullah M. (Frontiers in Cellular and Infection Microbiology, 2021)
Wheat is among the ten top and most widely grown crops in the world. Several diseases cause losses in wheat production in different parts of the world. Bipolaris sorokiniana (teleomorph, Cochliobolus sativus) is one of the wheat pathogens that can attack all wheat parts, including seeds, roots, shoots and leaves. Black point, root rot, crown rot and spot blotch are the main diseases caused by B. sorokiniana in wheat. Seed infection by B. sorokiniana can result in black point disease, reducing seed quality and seed germination and is considered a main source of inoculum for diseases such as common root rot and spot blotch. Root rot and crown rot diseases, which result from soil-borne or seed-borne inoculum, can result in yield losses in wheat. Spot blotch disease affects wheat in different parts of the world and cause significant losses in grain yield. This review paper summarizes the latest findings on B. sorokiniana, with a specific emphasis on management using genetic, chemical, cultural and biological control measures.